Wheels of life eaudiobook A user's guide to the chakra system. - Judith, Anodea (Tantor Media, 2014)
As portals between the physical and spiritual planes, the chakras offer unparalleled opportunities for growth, healing, and transformation. Anodea Judith's classic introduction to the chakra system, which has sold over 200,000 copies, has been completely updated and expanded. It includes revised chapters on relationships, evolution, and healing, and a new section on raising children with healthy chakras. Wheels of Life takes you on a powerful journey through progressively transcendent levels of consciousness. View this ancient metaphysical system through the light of new metaphors, ranging from quantum physics to child development. Learn how to explore and balance your own chakras using poetic meditations and simple yoga movements—along with gaining spiritual wisdom, you'll experience better health, more energy, enhanced creativity, and the ability to manifest your dreams.